Temporal dynamics of climate sensitivity of litter decomposition in a semi-arid grassland - Zhen Li; Fuwei Wang; Yue Wen; Chenglong Ye; Peng Wang; Tongshuo Bai; Xudong Gu; Liang Guo; Yunpeng Qiu; Yi Zhang; Yi Wang; Shuijin Hu (Geoderma)
Climate warming, precipitation changes, and reactive nitrogen (N) input are important environmental changes that can critically affect litter decomposition and soil carbon (C) dynamics. However, it remains unclear whether and how their effects and/or relative contribution vary across different decomposition stages. We assessed the effects of warming, precipitation changes and N addition, alone and in combination, on litter loss at various stages of the decomposition process in a semi-arid grassland. We found that warming inhibited litter decomposition in the early stage (1–2 years) and promoted it in the later stage (3–4 years). The temperature sensitivity of decomposition was affected by both soil moisture and N addition. Increased precipitation significantly accelerated litter decomposition initially, but not in the later stages. In the litter-soil incubation experiment, we observed that high-quality litter, characterized by low carbohydrate C:methoxyl C (CC:MC) ratio and/or CN ratios, displayed greater sensitivity to changes in moisture. In comparison, low-quality litter exhibits high temperature sensitivity of microbial respiration. Overall, our findings show that the climate sensitivity of litter decomposition exhibited distinct temporal dynamics, with increasing warming sensitivity of decomposition and decreasing moisture sensitivity of decomposition over time. Given that many current decomposition models use a constant sensitivity parameter (e.g., Q10 value = 2.0) throughout the decay process, our results suggest that incorporation of such temporal dynamics into decomposition models may enhance their predictive power.